Computer-assisted instruction with virtual reality: Exploring its impact on science learning and gender differences - Yılmaz Özkan; Enes A. Bilgin; Güneş Uğraş (Journal of Pedagogical Research)
The purpose of this study was to investigate the impact of computer-assisted instruction [CAI], incorporating virtual reality [VR], on the academic achievement of 6th-grade students in Science courses. The research employed a quasi-experimental design with a pre-test and post-test control group. Lessons in both experimental and control groups were conducted according to the 5E instructional model. While the experimental group utilized CAI, including VR, the control group followed traditional teaching methods. The study involved 52 students at a public school in the eastern region of Türkiye. A researcher-developed achievement test on the Respiratory System was used as the primary data collection tool. Quantitative data were analyzed using descriptive statistics, dependent and independent t-tests, and the Mann-Whitney U test. Findings revealed that CAI significantly improved students’ academic achievement in Science, whereas gender did not affect performance outcomes. In the experimental group, there was no significant difference in achievement between students with or without personal computers. However, unexpectedly, students in the control group with personal computers outperformed those without. The study highlights the effectiveness of CAI, including VR, in enhancing academic performance and underscores the importance of equitable access to technological resources. These findings have implications for education policymakers, teachers, and parents aiming to improve Science education quality and promote equal learning opportunities through technological integration.